Protective effect by low-intensity downhill running training against muscle damage and oxidative stress after high-intensity downhill running in rats - YILDIRIM, AYSEL; BELVİRANLI, MUAZ; OKUDAN, NİLSEL (Anais da Academia Brasileira de Ciências, 2022)
This study examined the effects of low-intensity eccentric exercise training performed before high-intensity eccentric exercise on muscle damage markers, oxidative stress and antioxidant defense. Twenty-two rats were divided into 3 groups; control (CON; n = 6), high-intensity eccentric exercise (HE; n = 8) and low-intensity eccentric exercise training plus high-intensity eccentric exercise (LET + HE; n = 8). Rats in the HE group performed HE at once. Rats in the LET + HE group performed LET and then HE protocol was applied. Blood and vastus intermedius muscle samples were taken 24 hours after the last exercise session for analyses of muscle damage, oxidative stress, and antioxidant defense markers. Muscle damage markers were higher in the HE group than the CON (137%-488%) and the LET + HE groups (82%-110%) (P < 0.05). Oxidative stress marker was higher in the HE group than the CON (65%) and the LET + HE (50%) groups (P < 0.05). Antioxidant defense markers were higher in the LTE + HE group than the HE group (39%-51%) (P < 0.05). In conclusion, low-intensity eccentric exercise training performed before high-intensity eccentric exercise conferred a protective effect against muscle damage by reducing oxidative stress and increasing antioxidant defense.